Floral painting language on packaging towards female consumer acceptance of product packaging recycling strategy - Zou, Shasha (2024)
Packaging waste of various products has increased dramatically, leading to excessive accumulation of waste, which could be more conducive to sustainable development. The final disposal of product packaging needs to be considered in the design process from the beginning of the product packaging life cycle. Therefore, it is necessary to make product packaging distinctive, attract consumers' attention, promote packaging reuse, increase consumer acceptance, and reduce unnecessary landfills. This research uses case study methodology aiming to integrate the connotation of painting language to make it acceptable to consumers and thus improve the reusability of packaging. The research posits that integrating the connotation of painting language in a package could produce unique product packaging, which increasing consumers' acceptance could promote reusing product packaging. The researcher used her flower watercolor paintings as the unit of analysis. The data collection was divided into 3 phases. Firstly, interviews with seven manufacturers resulted in 85.7% agreeing with special-shaped, 100% agreeing with environmentally friendly material, and 85.7% agreeing that beautiful and practical product packaging is readily accepted by consumers. In addition, interviews with seven consumers resulted in 71.4% agreeing that bright and relaxed flower-and-bird paintings are more suitable for consumers to accept. From the interviews, the research found that 78.5% agreed with relaxed, beautiful artistic conception, lifelike-plot stories, and emotional expressions more suitable for aroma and beauty care products. Secondly, the research develops a methodology using the connotation and characteristics of painting language to create a product packaging design where five flower paintings were produced to meet the consumers' aesthetic preferences. The final third phase involved interviews with 21 female consumers about their acceptance of the different proposed packaging based on the five flower paintings. Results from these validation interviews found that different types of packaging with the connotation of painting language received consumers' acceptance of 71%-90% and indicated 86%-90% of probable reuse by the same consumers. This research is significant since the increase in consumers’ acceptance of different types of packaging that incorporate the language of flower watercolor painting could increase the reuse of a product’s packaging. Such reuse efficiently reduces 50% of unnecessary waste transportation to landfills, thereby improving healthy cities and the well-being of citizens. This study recommends that future studies explore other painting connotation languages covering other flowers and extend similar principles to include nonflower paintings.